PENGARUH KONSENTRASI PUPUK ORGANIK CAIR BIOBOOST TERHADAP PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - Lainawa, Walhidayat; Rahmi, Rahmi (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
Liquid organic fertilizer, derived from natural sources, enhances the physical, chemical, and biological properties of soil. In cocoa cultivation, the use of organic fertilizers like Bioboost is crucial for soil fertility. Bioboost is a biological fertilizer containing beneficial microorganisms that promote soil fertility through biochemical processes. This study aimed to evaluate the effects of different concentrations of Bioboost liquid organic fertilizer on the growth of cocoa seedlings. The research was conducted at the Agronomy Screen House, Faculty of Agriculture, Tadulako University, Palu, Central Sulawesi, from July to October 2021. A Randomized Block Design (RBD) was employed, with five levels of Bioboost concentrations: 0 ml/l (control), 5 ml/l, 10 ml/l, 15 ml/l, and 20 ml/l. The results indicated that a Bioboost concentration of 20 ml/l produced the most favorable outcomes across all observed growth parameters for cocoa seedlings.